PENGELOLAAN KELAS DALAM PEMBELAJARAN MATEMATIKA DI SMP SWASTA PEDESAAN - Kumening, Ayu Sulistya; Suparni, Suparni (Universitas Tanjungpura, 2024)
The success of the learning process is influenced by the existence of good classroom management from educators and students. The purpose of this research is to describe the classroom management strategy in learning mathematics in rural private junior high schools. This research method uses field research through a qualitative descriptive approach. The subjects in this study were class VII C students and mathematics educators at a rural private junior high school located in Bantul. Data collection techniques used in this study are observation, interviews, and documentation. This research was conducted through three stages, namely planning, implementation, and observation. The results of this study prove that classroom management planning is carried out by making learning implementation plans, arranging classroom facilities, and managing students. Implementation of classroom management is carried out by applying the procedures for the prevention dimension and the healing dimension procedure. Supervision of classroom management is carried out by educators and school principals. Factors supporting and inhibiting classroom management include factors of physical environmental conditions, emotional social conditions, and organizational conditions.